2021
DOI: 10.1080/21655979.2021.2005990
|View full text |Cite
|
Sign up to set email alerts
|

E2F transcription factor 1/small nucleolar RNA host gene 18/microRNA-338-5p/forkhead box D1: an important regulatory axis in glioma progression

Abstract: This study aims to probe the biological functions of long non-coding RNA small nucleolar RNA host gene 18 (SNHG18) on glioma cells and its underlying mechanism. In this study, SNHG18 expression in glioma tissues was quantified employing GEPIA database; quantitative real-time PCR was adopted to examine the expressions of SNHG18, microRNA-338-5p (miR-338-5p) and forkhead box D1 (FOXD1) mRNA in glioma tissues and cell lines; cell proliferation, migration and invasion were detected utilizing cell counting kit-8, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It has been previously reported that SNHG18 is transactivated by megakaryocytic leukaemia 1 in non-small cell lung cancers 33 and E2F transcription factor 1 in glioma. 75 However, our unpublished data showed that none of these were impacted in serum-starved VSMCs by TGFβ1 treatment. Instead, we confirmed a critical role for Sp1 in SNHG18 transcriptional regulation in VSMCs.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It has been previously reported that SNHG18 is transactivated by megakaryocytic leukaemia 1 in non-small cell lung cancers 33 and E2F transcription factor 1 in glioma. 75 However, our unpublished data showed that none of these were impacted in serum-starved VSMCs by TGFβ1 treatment. Instead, we confirmed a critical role for Sp1 in SNHG18 transcriptional regulation in VSMCs.…”
Section: Discussionmentioning
confidence: 90%
“…Another study showed that SNHG18 accelerates glioma progression by regulating the miR-338-5p/FOXD1 (forkhead box D1) axis. 75 Similarly, it has been reported that SNHG18 facilitates non-small cell lung cancer growth and metastasis by modulating the miR-211-5p/BRD4 (bromodomain-containing protein 4) axis. 33 Conversely, SNHG18 has been suggested as a tumour suppressor and potential diagnostic biomarker in hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 80 Meanwhile, high expression of H19 leads to vincristine resistance in MM patients, in turn leading to poor prognosis. 50 SNHG18 promotes cell proliferation and metastasis in glioma 81 and nonsmall‐cell lung cancer. 82 It is also associated with poor prognosis in MM, 47 but the underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%